ANALISA PERFORMANSI QOS LAYANAN VIDEO STREAMING PADA JARINGAN MPLS-DIFFSERV DAN MPLS-INTSERV - Nurul Fadhilah; Sopian Soim; Lindawati Lindawati (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2018)
The telecommunications industry is constantly evolving and the demanding for a guarantee of applications services with better Quality of Service (QoS) continues to increase. This paper discusses the performance comparison of the QoS Method offered by Internet Engineering Task Force (IETF). The IETF introduces the QoS Differentiated Service (DiffServ) and Integrated Service (IntServ) Methods to ensure QoS. Both methods are integrated with Multi Protocol Label Switching (MPLS) technology to address the problem of traffic density and poor bandwidth allocation on the network. MPLS as a forwarding data technology used as a backbone which can improve QoS by labeling the IP address of the router. The comparison of MPLS-DiffServ and MPLS-IntServ method is done by measuring QoS parameter in the form of delay. The measured application is a Video Streaming with bitrate of 309 Kbps in 2 Mbps and 5 Mbps bandwidth variations. Bandwidth setting is performed to see the reliability of the MPLS-DiffServ and MPLS-IntServ network in conditions without traffic and with traffic load. Simulation results from GNS3 showed that MPLS-IntServ is a service with smaller delay than MPLS-DiffServ on conditions without traffic while on the network with the addition of traffic load, MPLS-DiffServ has a smaller delay than MPLS-IntServ.